Kinetic Behavior of Salmonella on Low NaNO(2) Sausages during Aerobic and Vacuum Storage - Ha, Jimyeong (Korean J Food Sci Anim Resour, 2016)
This study evaluated the growth kinetics of Salmonella spp. in processed meat products formulated with low sodium nitrite (NaNO(2)). A 5-strain mixture of Salmonella spp. was inoculated on 25-g samples of sausages formulated with sodium chloride (NaCl) (1.0%, 1.25%, and 1.5%) and NaNO(2) (0 and 10 ppm) followed by aerobic or vacuum storage at 10℃ and 15℃ for up to 816 h or 408 h, respectively. The bacterial cell counts were enumerated on xylose lysine deoxycholate agar, and the modified Gompertz model was fitted to the Salmonella cell counts to calculate the kinetic parameters as a function of NaCl concentration on the growth rate (GR; Log CFU/g/h) and lag phase duration (LPD; h). A linear equation was then fitted to the parameters to evaluate the effect of NaCl concentration on the kinetic parameters. The GR values of Salmonella on sausages were higher (p<0.05) with 10 ppm NaNO(2) concentration than with 0 ppm NaNO(2). The GR values of Salmonella decreased (p<0.05) as NaCl concentration increased, especially at 10℃. This result indicates that 10 ppm NaNO(2) may increase Salmonella growth at low NaCl concentrations, and that NaCl plays an important role in inhibiting Salmonella growth in sausages with low NaNO(2).